Teknik Intracytoplasmic Sperm Injection (ICSI) pada In Vitro Fertilization (IVF) untuk Mengatasi Penyebab Infertilitas - Hartini, Prastuti Dwi (Universitas Sebelas Maret, 2023)
Infertility is identified as a global health problem in couples who have difficulty having children or fail to have children naturally, so they have to go to a specialist doctor for consultation and even have to be treated using simple techniques or using sophisticated and modern technology. This meta-analysis study aims to obtain an overview of the intra cytoplasmic sperm injection (ICSI) technique in in vitro fertilization (IVF) as a solution to overcome the causes of infertility for married couples to have children. Method: by searching articles and scientific papers using the Google Scholar application. The conclusion is that the ICSI technique in IVF is indicated to be able to overcome problems that cause infertility for both men and women with a higher fertilization rate (64.3%) compared to conventional IVF methods (37.4%).